Song for a King's Exile: Royalism and Popular Music in Postcolonial Uganda. Issue 1 (1st January 2017) - Pier, David
Abstract: In 1971, Uganda's President Idi Amin arranged for the return of the body of Kabaka Edward Muteesa II from Britain, where it had been temporarily interred since the king's death in that country two years earlier. That year, Dan Mugula, pioneer of the kadongo kamu pop music genre, composed "Muteesa, Baalaba Taliiwo Buganda, " a song that expressed the grief and resentment people of the Baganda ethnicity had been feeling since their king was forced into exile in 1966. Nearly four decades later, in 2010, this old song surfaced again on YouTube, now with a new music video showing recent acts of police brutality and the desecration of a royal monument. Focusing on this song and its recent digital re-contextualization, this article explores how music can work to bring a past historical crisis into the living present, giving the community that experienced that crisis a reassuring, if fatalistic, sense of its own historical continuity.